Contribution of Women in the Education Management of Islamic Boarding School - Wardiana, Wina; Fadli, Adi; Masnun, Masnun (Ulumuna, 2024)
This study investigates the crucial role of women in managing Islamic boarding school education to facilitate the transformation of Islamic teaching. Using a qualitative approach centered on a literature review, data were gathered by analyzing relevant sources, articles and books. The research involved gathering, refining, organizing, and discussing selected materials to explore womens’ role and contribution in Islamic education. The findings of this study highlight women's significant contributions to boarding school management as caregivers, trainers, and mentors, impacting policies and decision-making. Various leadership styles, including democratic, charismatic, and paternalistic approaches, influence the school's development. Women also contribute to creating a conducive learning environment and promoting gender equality through inclusive programs in Islamic education.